Clinical outcome of lumbar microdiscectomy in patients with prolapsed lumbar intervertebral disc - Amir, A. B. M. Rashedul; Islam, M. Mominul; Ali, M. Raihan; Hossain, M. Mobaraque; Islam, M. Zahurul; Sultana, Nahida (International Journal of Research in Orthopaedics, 2026)
Background: Prolapsed lumbar intervertebral disc (PLID) is a common cause of low back pain and radiculopathy, often requiring surgical intervention when conservative management fails. Lumbar microdiscectomy is a widely accepted minimally invasive procedure for symptomatic relief, yet long-term outcome data in Bangladeshi populations remain limited. Methods: This retrospective observational study was conducted across multiple orthopedic centers in Rangpur City, Bangladesh, from January 2010 to December 2024. A total of 500 patients with clinically and radiologically confirmed PLID who underwent lumbar microdiscectomy were included. Demographic, clinical, radiological, operative and postoperative data were collected and analyzed using SPSS version 25. Outcomes assessed included pain relief, neurological recovery, complications and length of hospital stay. Results: The mean age of patients was 45.1±9.3 years, with males predominating (63.4%). Manual laborers comprised the largest occupational group (36.6%). Low back pain and leg pain/radiculopathy were the most common presenting symptoms (100% and 93.6%, respectively), while sensory disturbances were reported in 61.4% and motor weakness in 27.8%. MRI showed L4-L5 as the most commonly affected level (57.4%), with disc extrusion predominating (51.8%). Unilateral microdiscectomy was performed in 90.4% of cases, with a mean operative time of 56.1±11.9 minutes and mean blood loss of 82.7±26.4 ml. Postoperatively, excellent and good pain relief was achieved in 69.4% and 22.6% of patients, respectively. Complete neurological recovery occurred in 75.4%, with a low complication rate. The mean hospital stay was 3.5±1.5 days. Conclusions: Lumbar microdiscectomy is a safe and effective procedure for PLID, providing substantial pain relief and neurological improvement with minimal complications and short hospitalization.